Description of a new species of Aphlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) from southwestern China - Zhang, Hui; Bian, Xun (Zootaxa, 2025)
One new species of the endemic Chinese genus Aphlugiolopsis Wang & Li, 2015 is described based on the male specimen collected from Gaoligong Shan, Yunnan, China: A. gaoligongshanensis sp. nov. A key to the species of the genus is provided. The type specimen is deposited in Guangxi Normal University (GXNU).